Stability of shells of revolution made of a composite with fiber reinforcement subject to long-term damage - Khoroshun, L. P.; Babich, D. V. (International applied mechanics, 2010)
The problem of bifurcational instability of shells of revolution made of composite materials with fiber reinforcement subject to long-term damage is formulated and solved. A problem-solving method is developed